Polarization and convergence in socio-economic spatial development models - Korenik, Stanisław (Polaryzacja i konwergencja w społeczno-gospodarczych modelach zagospodarowania przestrzennego, 2020)
The basic economic category that is analysed in modern economy is growth. Referring this phenomenon to socio-economic space, the problem of its uniformity arises. In spatial development concepts, it is assumed to self-align this phenomenon (neoliberal concepts) or to force it through interventionism (Keynesian concepts). However, phenomena such as polarization and convergence occur in all considerations. These phenomena are perceived differently in diverse theories and doctrines, which is the reason they have different meanings and expectations
Biblioteka Regionalisty, 2020, Nr 20, s. 59-69
Keywords: economic growth and development; socio-economic space; polarization; convergence; wzrost i rozwój gospodarczy; przestrzeń społeczno-ekonomiczna; polaryzacja; konwergencja